1987
DOI: 10.1152/ajpheart.1987.253.5.h1199
|View full text |Cite
|
Sign up to set email alerts
|

Does inadequate oxygen delivery trigger pressor response to muscle hypoperfusion during exercise?

Abstract: In dogs running on a treadmill at 2 or 4 mph or 4 mph plus 10% incline, graded reductions in hindlimb perfusion reflexly elicited pressor responses. To test the idea that systemic arterial pressure (SAP) is raised by accumulation in muscle of a nerve-activating "pressor substance" release when O2 delivery becomes inadequate, arterial O2 content (CaO2) was reduced 29.1% by carbon monoxide (CO) inhalation before repeating exercise at 2 mph. We reasoned that the pressor substance, or related substances, should ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 0 publications
7
54
1
Order By: Relevance
“…In anesthetized animals, lactic acid has been shown to stimulate muscle afferents (22,23) and reflexly increase arterial pressure (24). In conscious dogs, the pressor response to progressive muscle ischemia during treadmill exercise was strongly correlated to venous effluent pH (25). In normal humans, we previously found a close temporal relationship between decreases in forearm muscle cell pH and increases in peroneal MSNA during static handgrip (12), an observation that we now have replicated in the present experiments.…”
Section: Resultssupporting
confidence: 81%
“…In anesthetized animals, lactic acid has been shown to stimulate muscle afferents (22,23) and reflexly increase arterial pressure (24). In conscious dogs, the pressor response to progressive muscle ischemia during treadmill exercise was strongly correlated to venous effluent pH (25). In normal humans, we previously found a close temporal relationship between decreases in forearm muscle cell pH and increases in peroneal MSNA during static handgrip (12), an observation that we now have replicated in the present experiments.…”
Section: Resultssupporting
confidence: 81%
“…In conscious dogs, the arterial pressure response to progressive muscle ischemia during exercise was highly correlated with venous effluent pH (20). Taken finding because previous observations had suggested that chemosensitive muscle afferents might be activated by some ofthe same metabolites that stimulate mitochondrial respiration (21).…”
Section: Discussionsupporting
confidence: 57%
“…This suggests that humans rely on local vasodilator mechanisms, and not a reflex increase in pressure, to restore blood flow to hypoperfused contracting muscle. In contrast, there is overwhelming evidence that suggests a pressor response is essential in the restoration of blood flow to underperfused hindlimbs of exercising dogs (12,22,23,30,35). The discrepant findings between our series of studies in humans and those performed in dogs may simply be related to species differences.…”
Section: Restoration Of Flow Via Local Vasodilator Mechanismscontrasting
confidence: 58%